Antibiotic activity of Emerimicin IV isolated from Emericellopsis minima from Talcahuano Bay, Chile. Issue 11 (3rd June 2018) - Inostroza, Alejandro; Lara, Liliana; Paz, Cristian; Perez, Andrés; Galleguillos, Felipe; Hernandez, Victor; Becerra, José; González-Rocha, Gerardo; Silva, Mario
Abstract: Due to the increasing emergence of resistance of bacterial pathogens to current antibiotics, we have examined the marine fungi present in sea sediments obtained 200 m offshore to discover new antibacterial compounds active against multidrug-resistant bacteria. One strain, identified as Emericellopsis minima, was isolated from sediments of Talcahuano Bay (Chile). From the liquid culture of E. minima, we isolated Emerimicin IV, a unique fungal peptaibol that exhibited antibacterial activity. The structure of this compound was assigned by interpretation of 1 H NMR and HR-LCMS data. Emerimicin IV showed bacteriostatic activity against clinical isolates of methicillin-resistant Staphylococcus aureus and vancomycin-resistant Enterococcus faecalis with MIC values ranging between 100 and 12.5 μg/mL. Abstract :